Effect of Biochar Type in the Performance of Biochar-Modified Binder - Sanchez, Xiomara; Varamini, Sina (Revista Ingeniería de Construcción, 2024)
Biochar is obtained from the thermochemical conversion of biomass and stores carbon in a stable form. Adding biochar to asphalt could enable carbon offsetting. Biomass sources and pyrolysis technologies yield biochar with different chemical and physical characteristics. This study investigated the effect of two types of wood biochar on the binder characteristics. 5% and 10% biochar were added to a PG 58S-28 asphalt. Four biochar-modified binders and one control were characterized using rotational viscosity, penetration, frequency sweep tests, and Fourier-transformed infrared spectroscopy (FTIR). The results indicate that biochar increases the viscosity and reduces the penetration. The rheological analysis suggests that biochar could increase the rutting resistance but decrease the cracking resistance. Additionally, biochar alters the oxidative ageing of the binders. This study demonstrated that the biochar type impacts the binder performance, and source and content should be considered to understand the effect and determine the dosage of biochar to asphalt.